ANALISIS PENGARUH KEBIJAKAN DIVIDEN, KEBIJAKAN HUTANG, PROFITABILITAS DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN TAHUN 2015 – 2017 (Studi pada perusahaan manufaktur yang terdaftar di BEI 2015 - 2017) - Fitri Ratnasari, 15.05.52.0162; Wahyu Widati, Listyorini (Students' Journal of Accounting and Banking, 2019)
This study aims to examine Analysis of the effect of Dividend Policy, Debt Policy, Profitability, and Investment decisions on Firm Value in Manufacturing companies on the Indonesia Stock Exchange for the period 2015-2017. The sample selection technique used a purposive sample and obtained 38 companies with a period of 3 years so that 114 data were obtained, and processed using the SPSS application. Based on the results of data processing, it was found Debt Policy, Profitability, and Investment decisions variables have a positive and significant effect on Firm Value While Dividend Policy did not affect the Firm Value. The results of the test on the coefficient of determination (R2) are 0.831. This means that 83.10% is Debt Policy, Profitability, and Investment decisions and tax while the remaining 16.90% is influenced by other variables.